Decentralized sliding mode control for an electrohydraulic robot manipulator - Ishak, Haszuraidah (2007)
This thesis is concerned with the problems of modelling and controlling of a 3 DOF electrohydraulic robot manipulators. The control of electrohydraulic robot manipulator is challenging due to the dependence of system parameters on variables such as displacement and velocity, on the geometry and inertia of the links, uncertainties associated with gravity, coriolis and centrifugal forces, variations in payload handled by the manipulator, and environmental influences. To overcome these problems, an integrated mathematical model of the 3 DOF electrohydraulic robot manipulators is treated as a large-scale uncertain system models using the known parameters of the robot. Decentralized control concept is used in this study where the uncertain system is treated as large-scale system which composed of a set of interconnected uncertain subsystems. A variable structure control (VSC) strategy is utilized to overcome the inherent high nonlinearity in the system dynamics under decentralized and centralized frameworks. In each of the approach, a variant of the VSC known as the Sliding Mode Control (SMC) is adopted to ensure the stability of the system dynamics during the sliding phase and to render that the system insensitive to the parametric variations and disturbances. The performance and robustness of the proposed controller is evaluated through computer simulation by using Matlab and Simulink. The results proved that the controller has successfully provided the necessary tracking control for the 3 DOF electrohydraulically driven robot manipulator system.